Updated physical-geographical zoning of the Kharkiv region - Максименко, Н. В; Квартенко, Р. О.; Різник, К. Ю. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2016)
The article contains a detailed analysis of the landscape structure of the Kharkiv region at physiographic regions, districts and regions in full compliance with the updated physical-geographical zoning of Ukraine. This can be the basis for further geographical and environmental studies.UDC